Mitigasi Bencana Melalui Desa Tangguh Bencana Di Kabupaten Badung Kelurahan Tanjung Benoa Provinsi Bali - Nadila watora; Agy Aswad Ilham (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
The author focuses on the Tanjung Benoa sub-district as an area with a tsunami red zone, so researchers see the need for a disaster-resilient village that has a complex set of organizational arrangements to build community awareness that is currently a vulnerability for the area. This study aims to identify and analyze disaster mitigation through disaster-resilient villages in Tanjung Benoa Village, Badung Regency, Bali Province. The method used in this study is a qualitative descriptive method with an inductive approach. The research results show that the local wisdom of the local community has a very big impact on the process of handling disasters in the Tanjung Benoa Village, Badung Regency, Bali Province. The results of this study follow the facts obtained from interviews with informants, and observation researchers in the Tanjung Benoa Village environment. Disaster mitigation through a disaster-resilient village in Tanjung Benoa Sub-District, Badung Regency, Bali Province is very encouraging with the UNESCO having a Tsunami Ready certificate because of local wisdom.